(untitled) (Research, Society and Development, 2020)
Objective: this study consisted of a survey of the number of cases/deaths from the coronavirus COVID-19 in the northwest macro-region of the state of Paraná, Brazil. Methodology: the data were obtained from Epidemiological Bulletins provided by the Health Department of the State of Paraná, from Notifica Coronavirus Program (COVID-19) in the period from March to September 2020. Information used from the regional health center of the northwest macro-region, which correspond to the 11th Campo Mourão Regional Health Center, 12th Umuarama Regional Health Center, 13th Cianorte Regional Health Center, 14th Paranavaí Regional Health Center and 15th Maringá Regional Health Center. Results: it was found that there was a linear increase in the reported cases of COVID-19 in the period evaluated in the five cities in the state of Paraná , with 177,007 people infected and 4,441 deaths throughout the state. The city with the highest number of cases/death was Maringá (13,256 cases and 225 deaths), and conversely Paranavaí (1668 cases and 41 deaths) had the lowest number of cases/deaths. There was a significant increase in the number of cases as of june/2020, justified by the mass testing of the population that started on May 29th, 2020, and by the beginning of the winter season in the southern region of Brazil, which causes every year high incidences of lung diseases. Conclusion: to date there is no effective treatment available, with a prognosis that until December/2020 there will be a vaccine to immunize the entire population.